![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
1个回答
展开全部
显然 x=0, y=1>0
若 x>0, y=a^x >0
若 x<0, -x>0, y=a^x=1/a^(-x) >0
所以 y=a^x >0
log(a)x过定点(1,0),
则y=log∨a(x+3)-1过定点A(-2,-1)。
代入mx+ny+1=0得:-2m-n+1=0,即
2m+n=1.
∴1/n+2/m=(2m+n)/n+(4m+2n)/m
=(2m/n)+(2n/m)+5
≥4+5=9,(均值不等式)
∴最小值9.
若 x>0, y=a^x >0
若 x<0, -x>0, y=a^x=1/a^(-x) >0
所以 y=a^x >0
log(a)x过定点(1,0),
则y=log∨a(x+3)-1过定点A(-2,-1)。
代入mx+ny+1=0得:-2m-n+1=0,即
2m+n=1.
∴1/n+2/m=(2m+n)/n+(4m+2n)/m
=(2m/n)+(2n/m)+5
≥4+5=9,(均值不等式)
∴最小值9.
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询